Gratification and Social Adjustment of Blind Children in District Faisalabad, Pakistan - Asim, Muhammad; Zafar, Aisha; Batool, Zahira; Jamal, Atif (Richtmann Publishing, 2012)
Most of the blind people live in the developing countries with the blindness rate 10-20 times higher than thatdeveloped countries. Especially special children face many social and economic problems blind children. Such children want tohave special attention regarding their social adjustment. The study was designed to identify and analyze the need satisfactionand social adjustment of blind children in Faisalabad, Pakistan. The universe of the present study was particularly comprised ofblind educational institutions in Faisalabad. Eighty respondents were selected through convenient sampling technique. The datawere collected through well designed interview schedule. The study revealed that a large majority 78.8% of the respondents ofthe total reported that that they faced blindness since birth. A mainstream of the population 52.5% reported that their parentspaid attention during their sickness and 47.5% of the respondents reported that they discussed their personal problems with theirparents.